From Guardians to Threats? Abusive Judicial Review and Public Distrust - Fathi, Muhammad; Riyanto, Aisyah Ajeng Putri; Prasetyoningsih, Nanik; Amirullah, Muhammad Nur Rifqi (Fakultas Hukum Universitas Islam Indonesia, 2025)
This article investigates the crisis of public trust in Indonesia’s Constitutional Court, triggered by a series of controversial decisions that suggest the practice of abusive judicial review. It focuses on three pivotal rulings, Decision No. 90/PUU-XXI/2023, that collectively reveal a pattern of judicial behavior aligned with executive interests, undermining judicial independence and constitutional integrity. Utilizing a normative legal research method with statute, conceptual, and analytical approaches, the study critically examines how judicial overreach, ethical breaches, and procedural irregularities have contributed to institutional decay. The findings indicated that the Constitutional Court has shifted from its role as a counter-majoritarian institution to a political instrument, eroding legal certainty and democratic accountability. The involvement of justices in conflicts of interest, particularly in election-related cases, has intensified public skepticism and revealed systemic weaknesses in judicial appointment and oversight mechanisms. This paper argued that such decisions constitute a form of “abusive judicial review” that threatens Indonesia’s constitutional democracy. To restore judicial legitimacy, structural reforms are imperative, emphasizing transparent judicial recruitment, permanent ethical oversight bodies, and stronger civil society engagement. The article concluded that without substantial reform, the erosion of public trust may further delegitimize the Court as a guardian of the Constitution.